Comparison of Gaussian and Square Laser Pulses on Molecular Orientation (Journal of Atomic and Molecular Sciences, 2018)
To investigate the orientations of CO molecule driven by both Gaussian and square laser pulses, we give the theoretical analysis using the density matrix method and rigid rotor approximation. The results show that both pulses with a short duration can induce the in-pulse and post-pulse orientations easily, and that the field-free molecular orientation in both non-adiabatic and adiabatic regimes can be obtained by square laser pulse. In addition, the discussion of the temperature effect for field-free orientation shows that the square laser pulse is more feasible in an ensemble of higher temperature.